PRODUCT PACKAGING AND DIGITAL MARKETING TRAINING FOR MSME MEMBERS OF PDA NORTH LOMBOK - Zaenafi Ariani; Dina Soes Putri; Marianah; Surmini; Ariansyah; Nurul Hidayah (STKIP Citra Bakti, 2024)
The Aisyiyyah Regional Leadership (PDA) is one of the organisations under Muhammadiyah that has women members distributed across all provinces in Indonesia. One such organisation is the North Lombok PDA. The North Lombok PDA has a significant number of members who are micro-entrepreneurs, but they are still lacking in terms of product promotion. The objective of this service activity is to enhance the knowledge and skills of the North Lombok PDA members in the domains of product packaging and digital-based marketing. The methodology employed in this service activity is Participatory Action Research, wherein the partners assume an active role in the activity. The enhancement of the participants' knowledge and abilities was gauged through pre- and post-tests and practical assessments. The effectiveness of the service is evaluated through a satisfaction questionnaire completed by participants at the conclusion of the event. The service activity was conducted over a two-day period and was executed in an orderly and seamless manner. The results of the pre- and post-test data processing demonstrate that there was an increase in the participants' knowledge before and after they were given counselling material. The increase in participant knowledge was 25%. In conclusion, the results of the participant satisfaction questionnaire indicate that the service activity was a success. The participants' assessment per indicator was predominantly positive, with the majority scoring in the good and excellent categories.